Formation and Structural Characterization of Metal Complexes derived from Thiosalicylic acid - Bhowon, Minu G.; Jhaumeer-Laulloo, Sabina; Moosun, Salma; Humphreys, Lisa; Coles, Simon; Fowdram, Roshni; Mungra, Evena (Wiley, 2017)
The formation and structural aspects of some metal complexes of thiosalicylic acid (TSA) were studied. The µ-bridging tetra-coordinated Ru complex, [Ru(C6H4(CO2)(µ-S)(H2O)]2 (1) was formed by hydrothermal reaction of TSA with RuCl3. The complexes [M(dtdb)(phen)(H2O)]n (2-4) (M= Zn(II), Co(II), Ni(II), dtdb = 2,2’-dithiodibenzoate anion, phen = 1,10-phenanthroline) were obtained by the slow diffusion technique and the in situ S-S bond formation was confirmed by elemental, spectral and X-ray analysis. Reaction of TSA with CuCl2 and 2,2’-bipyridine (bipy) under the slow diffusion technique yielded the dimer [Cu(tdb)(bipy)] (5) (tdb = thiodibenzoic acid) where the in-situ generation of 2,2’-thiodibenzoic acid was observed.